Evaluation of Trimethoprim/Sulfamethoxazole (SXT), Minocycline, Tigecycline, Moxifloxacin, and Ceftazidime Alone and in Combinations for SXT-Susceptible and SXT-Resistant Stenotrophomonas maltophilia by In Vitro Time-Kill Experiments - Wei, Chuanqi (PLoS One, 2016)
BACKGROUND: The optimal therapy for infections caused by Stenotrophomonas maltophilia (S. maltophilia) has not yet been established. The objective of our study was to evaluate the efficacy of trimethoprim/sulfamethoxazole (SXT), minocycline, tigecycline, moxifloxacin, levofloxacin, ticarcillin-clavulanate, polymyxin E, chloramphenicol, and ceftazidime against clinical isolated S. maltophilia strains by susceptibility testing and carried out time-kill experiments in potential antimicrobials. METHODS: The agar dilution method was used to test susceptibility of nine candidate antimicrobials, and time-killing experiments were carried out to evaluate the efficacy of SXT, minocycline, tigecycline, moxifloxacin, levofloxacin, and ceftazidime both alone and in combinations at clinically relevant antimicrobial concentrations. RESULTS: The susceptibility to SXT, minocycline, tigecycline, moxifloxacin, levofloxacin, ticarcillin-clavulanate, chloramphenicol, polymyxin E, and ceftazidime were 93.8%, 95.0%, 83.8%, 80.0%, 76.3%, 76.3%, 37.5%, 22.5%, and 20.0% against 80 clinical consecutively isolated strains, respectively. Minocycline and tigecycline showed consistent active against 22 SXT-resistant strains. However, resistance rates were high in the remaining antimicrobial agents against SXT-resistant strains. In time-kill experiments, there were no synergisms in most drug combinations in time-kill experiments. SXT plus moxifloxacin displayed synergism when strains with low moxifloxacin MICs. Moxifloxacin plus Minocycline and moxifloxacin plus tigecycline displayed synergism in few strains. No antagonisms were found in these combinations. Overall, compared with single drug, the drug combinations demonstrated lower bacterial concentrations. Some combinations showed bactericidal activity. CONCLUSIONS: In S. maltophilia infections, susceptibility testing suggests that minocycline and SXT may be considered first-line therapeutic choices while tigecycline, moxifloxacin, levofloxacin, and ticarcillin-clavulanate may serve as second-line choices. Ceftazidime, colistin, and chloramphenicol show poor active against S. maltophilia. However, monotherapy is inadequate in infection management, especially in case of immunocompromised patients. Combination therapy, especially SXT plus moxifloxacin, may benefit than monotherapy in inhibiting or killing S. maltophilia.